STRATEGI GURU PAI DALAM MENCEGAH RADIKALISME DAN MENGEMBANGKAN SIKAP MODERASI BERAGAMA DI KALANGAN REMAJA - Resti Nurul Hidayah; Mustakim; Sandi Aqura Yoga; Dinda Wati; Mukhtar Latif (STKIP Subang, 2026)
Radicalism among adolescents is one of the challenges facing the education sector because it can influence the way they think, behave, and interact in society. Islamic Religious Education (PAI) teachers play a strategic role in preventing the spread of radical ideologies through a learning process that instills moderate, tolerant Islamic values and respect for diversity. This study aims to describe the strategies used by PAI teachers to prevent radicalism and foster religious moderation among adolescents. The study employs a qualitative approach using a literature review method. Data were obtained from various scholarly sources, including books, national and international journal articles, conference proceedings, and documents relevant to the research topic. Data analysis was conducted through data reduction, data presentation, and the drawing of descriptive conclusions. The study’s findings indicate that PAI teachers’ strategies for preventing radicalism involve integrating the values of religious moderation into instruction, strengthening character education, fostering attitudes of tolerance, developing critical thinking skills regarding religious information, setting a positive example through teachers’ behavior, and the wise use of digital media. Furthermore, collaboration among schools, families, and the community is a key factor in fostering an environment that supports the development of religious moderation. These strategies contribute to fostering mutual respect, rejecting violence committed in the name of religion, strengthening national spirit, and shaping the character of adolescents to be inclusive, tolerant, and capable of living harmoniously in a diverse society